(untitled) (Bisanzio e l’Occidente, 2018)
The Vendetta dei discendenti di Ettore is an anonymous and quaint literary pastiche, still unpublished, which blends the Trojan tradition with the Arthurian one. It was likely written between the end of the XIV and the beginning of the XV century, possibly in Lucca, before the Croniche by Giovanni Sercambi, who seems to have drawn inspiration from it in some brief chapters. It stages a kind of world war that involves, more than a thousand six hundred years after the fall of Troy, the descendants of Hector and the father of king Arthur, Uter Pendragon, joined by other knights of the Round Table and supported by Romans and Persians in a mission to exact revenge on Greeks and the new Greeks (the Byzantines). The text, probably inspired by the Roman de Perceforest, and always indebted to Wace’s Brut, singer of the translatio imperii, stages an epic clash between culture and nature, barbarism and civilization, employing a narrative rhythm sometimes unlikely and almost dreamlike, set in a kind of parallel universe rich in contradictions that can be interpreted using Matte Blanco’s bi-logic. These notable features let us forget the humble literary quality of the text.